ANALISIS KONTRIBUSI UMKM TERHADAP TENAGA KERJA DAN EKSPOR - Najeeb Muizz; Majdi Zaabit (Birokrasi: JURNAL ILMU HUKUM DAN TATA NEGARA, 2023)
MSME business performance has not been very encouraging due to various obstacles and weaknesses in managing the business and the lack of capital support to support the business. Attention to growing micro, small and medium enterprises (MSMEs) is based on at least three reasons. First, MSMEs as a survival strategy in times of economic downturn. The second reason, the tendency to absorb a lot of labor force makes many MSMEs also intensive in using local natural resources. The progress of MSMEs in reducing poverty and equalizing people's income.